The Influence of Income on Employee Performance at CV. X - Muhammad irfan lubis (International Journal of Business and Quality Research, 2023)
The quality of employee performance is affected by the amount of wages and allowance provided by the company. Amount of salary earned by employees in CV. X is directly proportional to the quality of work performance. The aim of this research is to find out how the amount of salary earned affects the performance of employees in CV. X. The technique used in collecting data is through observations, interviews, and questionnaires. The type of data used in this research is qualitative data. Data samples are taken by using a random sampling technique with 10 indicator questions. The amount of samples used is 70 respondents. This research uses qualitative data analysis obtained from interviews, observations, and questionnaires. Based on the result obtained on this research, the amount of salary affects the quality of the employees' performance.